Political Corruption in Libya: Diagnosis of Manifestations and Effects Amid Instability, and Proposal of Counter-Strategies - Hamida Ali Ismail (Journal of Scientific and Human Dimensions, 2025)
This research aims to clarify the manifestations and forms of corruption, focusing on political corruption, which is classified as the most dangerous. This scholarly effort seeks to survey the reality and diagnose the phenomenon in Libyan society under conditions of political instability, weak institutions, and chaos. The research discusses the causes and factors of corruption, and the destructive effects of political corruption on institutional, social, economic, political, and legal aspects. The study proposes means of confrontation and treatment, reviewing political corruption counter-strategies , including the role of systems and laws, awareness and media, institutional reform, judicial independence, and community participation, in addition to the effective role of Islamic Sharia in combating it.
Keywords: Political Corruption; Anti-Corruption; Libya; Political Instability; Islamic Sharia